1991
DOI: 10.1089/sct.1991.7.93
|View full text |Cite
|
Sign up to set email alerts
|

Reduction by Norepinephrine of the Side Effects Induced by Combined Hepatic Arterial Administration of Degradable Starch Microspheres and Adriamycin in Rats with a Liver Adenocarcinoma

Abstract: In previous studies we found degradable starch microspheres (DSM) to increase the antitumor effect of adriamycin injected by the hepatic artery in rats with a liver adenocarcinoma. Increased side effects also appeared, namely body weight loss and liver necroses. In the present paper, norepinephrine in four different protocols was added to the injection of adriamycin + DSM to decrease the drug flow to normal tissues. In two protocols norepinephrine decreased the body weight loss. There was also a non-significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1994
1994

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Furthermore, the duration of the vascular occlusion was not monitored, as usually done in the clinical situation but the microspheres were injected in a standardized manner in all animals. Following the standardized rapid injection of microspheres in pharmacological studies using the same DSM dose as in the present study, regional adverse effects, such as GI-toxicity, have been reported (7). Rapidly injecting large amounts of DSM blocks the hepatic artery, forcing the microspheres into the splanchnic circulation where they may temporarily occlude splanchnic organs.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, the duration of the vascular occlusion was not monitored, as usually done in the clinical situation but the microspheres were injected in a standardized manner in all animals. Following the standardized rapid injection of microspheres in pharmacological studies using the same DSM dose as in the present study, regional adverse effects, such as GI-toxicity, have been reported (7). Rapidly injecting large amounts of DSM blocks the hepatic artery, forcing the microspheres into the splanchnic circulation where they may temporarily occlude splanchnic organs.…”
Section: Discussionmentioning
confidence: 67%